Segregating cognitive functions within hippocampal formation: A quantitative meta‐analysis on spatial navigation and episodic memory - Kühn, Simone (Hum Brain Mapp, 2013)
The most important cognitive domains where hippocampal formation is crucially involved are navigation and memory. Some evidence suggests that different hippocampal subregions mediate these domains. However, a quantitative meta‐analysis on neuroimaging studies of spatial navigation versus memory is lacking. By means of activation likelihood estimation (ALE), we investigate concurrence of brain regions activated during spatial navigation encoding and retrieval as well as during episodic memory encoding and retrieval tasks in humans. During encoding in spatial navigation, activity was located in more posterior regions of the hippocampal formation, whereas episodic memory encoding was located in more anterior regions. Retrieval in spatial navigation was more strongly lateralized to the right compared to episodic memory retrieval. Within studies on spatial navigation retrieval, immediate recall was located more posterior and delayed recall more anterior. Overlap between concurrence of activation in spatial navigation and episodic memory was rather limited in comparison to uniquely involved regions. This argues in favor of two distinct networks, one for spatial navigation the other for episodic memory within the hippocampal formation. Hum Brain Mapp 35:1129–1142, 2014. © 2013 Wiley Periodicals, Inc.